Eigenvalue analysis for high telecommunication towers with lognormal stiffness by the response function method and SFEM - Kamiński, Marcin Marek; Szafran, Jacek (Computer Assisted Methods in Engineering and Science, 2017)
The main aim of this paper is to demonstrate the application of the generalized stochastic perturbation technique to model the lognormal random variables in structural mechanics. This is done to study probabilistic characteristics of the eigenvibrations for the high telecommunication towers with random stiffness, which are modeled as the linear elastic 3D trusses. The generalized perturbation technique based on the Taylor expansion is implemented using the Stochastic Finite Element Method in its Response Function version. The main difficulty here, in a comparison to this technique previous applications, is a necessity of both odd and even order terms inclusion in all the Taylor expansions. The hybrid numerical approach combines the traditional FEM advantages with the symbolic computing and its visualization power and it enables for a verification of probabilistic convergence of the entire computational procedure.